'True and Pious Men': Anglican Ministry to Chinese Settlers in Southern Queensland, 1850–1914. Issue 2 (April 2020) - LE COUTEUR, HOWARD
Abstract : Chinese men began emigrating to the Australian colonies from the 1840s onward. Past historiography has been sceptical of the impact of Christianity on these Chinese immigrants. This paper revisits this theme, placing it in the wider context of mission to Chinese immigrants in other anglophone countries. It documents the ministry of the Anglican Church among Chinese settlers in colonial Queensland, and especially the role that Chinese converts played in the evangelisation of their fellow countrymen. It provides a new perspective on the ways in which the Chinese embraced Christianity, and their contribution to the evangelisation of their countrymen.